A Laughing Matter: Patterns of Laughter and the Effectiveness of Working Dyads - Wang, Lu; Doucet, Lorna; Waller, Mary; Sanders, Karin; Phillips, Sybil (Organization Science, 2016)
Poor communication in teams has been found to result in disappointing team performance. Integrating research on team communication and laughter, we tested hypotheses about the relationship between working dyads’ patterns of laughter and their open communication and effectiveness. We examined two patterns of laughter: shared laughter occurs when both individuals laugh frequently in a dyad, and unshared laughter occurs when one individual in a dyad laughs frequently, but the other does not. Using data collected from 93 flight simulations in two aviation courses, we found that dyads engage in more open communication and are more effective when one member laughs frequently, but the other member does not. In addition, we found that the agreeableness of a dyad member reduces team effectiveness by increasing the likelihood of shared laughter. These results highlight the important role of laughter in team interactions and expand the growing literature on the role of emotions in teams.